Yizani Sifunde: Lessons from a successful multi-NGO collaboration - von Blottnitz, Magali (Liberty Community Trust, Wordworks, Book Dash and Nal'ibali, 2024)
This is the second in a series of learning briefs that explore the design, implementation and impact of Yizani Sifunde, a collaborative multi-pronged intervention designed to boost early literacy outcomes in 4- and 5-year-olds. The intervention was co-delivered by three leading South African NGOs, with two regional NGOs implementing part of the project locally. This brief focuses on: • the experience of the collaboration; and • the factors and practices that made it successful. In particular, it highlights the role played by the funder, Liberty Community Trust, the importance of clearly defined roles and collaboration modalities between project partners, and the learning mindset that helped improve the project design and adjust to unforeseen realities especially during the Covid-19 pandemic.
Exploring the impact of a collaborative, multi-pronged early literacy intervention on 4- and 5-year-olds - Brief 2
Yizani Sifunde (isiXhosa for “come, let’s read”) aimed to boost early literacy outcomes at under-resourced early childhood development (ECD) centres in the Eastern Cape. It was implemented in three one-year cycles between 2021 and 2023. The project was initiated and funded by the Liberty Community Trust, and jointly designed and delivered by three literacy nonprofits: Book Dash, Nal’ibali and Wordworks. Local Eastern Cape partners ITEC and Khululeka supported implementation. More information about Yizani Sifunde is available on the Book Dash website https://bookdash.org/yizani-sifunde/
Keywords: Early learning; Early literacy; Early Childhood Development; Yizani Sifunde; South Africa; Eastern Cape; ECD centres; Liberty Community Trust; Wordworks; Nal'ibali; Book Dash; Khululeka; ITEC; Pre-Grade R; Collaboration; Children's Books; Book ownership; Little Stars; Story Sparkers; Reading; Monitoring and Evaluation; Reflection